(untitled) (Journal of Basic and Applied Research in Biomedicine, 2024)
Background: Chronic inflammation, immune system dysfunction and elevation in the levels of toxic metals such as lead (Pb) are common observations in patients with substance use disorders (SUD). However, there is little information on the acute phase profile of SUD patients with different serum levels of Pb. Therefore, serum levels of selected acute phase proteins in SUD patients with different serum levels of Pb were determined in this study. Methods: A total of 84 adults consisting of 45 patients with SUDs and 39 controls were enrolled into this case-control study. Serum levels of Pb, albumin and C-reactive protein (CRP) were determined using Atomic Absorption Spectrophotometer, bromocresol green (BCG) colorimetric method, and ELISA, respectively. Thereafter, CRP-albumin ratio (CAR) was calculated as appropriate. Results: Serum levels of Pb and albumin were significantly higher in patients with SUDs compared with the controls. Considering variation in acute phase proteins based on Pb level, the serum level of albumin was significantly lower, while the serum CRP level and CAR were slightly higher in patients with SUDs whose Pb level was higher than 5 µg/dL compared with patients whose Pb level was ≤5 µg/dL. No significant differences were observed in the levels of Pb, albumin, CRP, CAR in patients with SUDs who abuse single substance compared with those who abuse multiple substances. Conclusion: SUD is associated with increased serum levels of Pb and albumin, and alteration in the serum levels of acute phase proteins appears to be influenced by the serum Pb level. Therefore, there is the need for routine measurement of Pb level in patients with SUDs as they could benefit from therapeutic interventions involving chelation of Pb which could prevent disordered acute phase responses in the patients and facilitate optimal response to antipsychotics.